STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK KELAS V MI MA'ARIF NU MAMBAUL ULUM GEMPOL BENJENG - Muhammad Thoha (PEDIR: Journal of Elementary Education, 2022)
A learning strategy is a plan that contains a series of learning activities that are specifically designed both in terms of methods and their use to achieve educational goals. Therefore, to achieve the desired educational goals in learning. Teachers are expected to have several learning strategies in order to increase student motivation. The research focus in this study is how the teacher's strategy in increasing the motivation to learn Aqidah Akhlak at MI Ma'arif NU Mambaul Ulum Gempol Benjeng, what are the supporting and inhibiting factors faced by teachers in increasing motivation to learn Aqidah Akhlak at MI Ma'arif NU Mambaul Ulum Gempol Benjeng. In this study, the authors used a type of qualitative research with a case study approach. Data collected through observation, interviews and documentation. The validity of the data by means of triangulation. The results of the research found at the research location show that the success of Aqidah Akhlak teachers in increasing student learning motivation is good and increasing. This can be seen from the students who are lazy to study, become active in learning and read a lot and dare to express opinions in the learning process. Then in increasing the motivation to study Aqidah Akhlak there were a number of obstacles experienced by MI Ma'arif NU Mambaul Ulum Gempol Benjeng teachers. However, the obstacles experienced by teachers can be minimized with the support of parents of students, the ability of teachers to use learning media. The conclusion in this study is that the teacher has an expository strategy and an inquiry strategy in increasing learning motivation, there are a number of obstacles felt by the teacher in increasing student learning motivation, as well as the existence of supporting factors such as support from parents of students who can help teachers in increasing motivation to learn Aqidah Akhlak.